Merdeka Belajar: a New Paradigm of Islamic Education in the Setting of Social Change - Ach. Syaiful; Pahar Kurniadi; Mufiqur Rahman (TADRIS: Jurnal Pendidikan Islam, 2022)
Social change is an inseparable part of Islamic education with a new paradigm. These changes have strong implications in the educational order that demands a more humanist and liberating education system. Freedom of learning is an educational concept that offers a new direction that allows the implementation of education to be carried out autonomously and decentralized. The policies launched in this concept carry a mission to free education from the shackles of administrative-formalistic aspects. The implementation of this policy package resulted in essential changes including; 1) Minimum Competency Assessment (AKM); 2) Character Survey; 3) Study Environment Survey.